Emergence of Ixodes scapularis and Borrelia burgdorferi, the Lyme disease vector and agent, in Ohio - Wang, Peng; Glowacki, Meaghan N.; Hoet, Armando E.; Needham, Glen R.; Smith, Kathleen A.; Gary, Richard E.; Li, Xin (Frontiers in Cellular and Infection Microbiology, 2014)
Lyme disease, the most common vector-borne disease in the United States, is caused by a tick-borne infection with Borrelia burgdorferi. Currently, Ohio is considered by the Centers for Disease Control and Prevention (CDC) to be non-endemic for Lyme disease. The low incidence of Lyme disease in this state was largely attributed to the absence of the transmitting vector, Ixodes scapularis, commonly known as the blacklegged tick. However, a tick surveillance program established by Ohio Department of Health indicated that the number of I. scapularis in Ohio had increased sharply in recent years, from 0 - 5 ticks per year during 1983–2008 to 15 in 2009, 40 in 2010, and 184 in 2011. During the fall deer hunting season, examination of deer heads submitted to Ohio Department of Agriculture found 29 I. scapularis from 7 counties in 2010 and 1,830 from 25 counties in 2011. As of 2012, the tick had been found in 57 of the 88 counties of Ohio. In addition, all three active stages (larva, nymph, and adult) of I. scapularis were found in Tiverton Township of Coshocton County, demonstrating the presence of established tick populations at this central Ohio location. Of 530 nymphal or adult I. scapularis analyzed by quantitative polymerase chain reaction (qPCR), 32 (6.1%) tested positive for the B. burgdorferi flaB gene, ranging from 36 to 390,000 copies per tick. Antibodies to B. burgdorferi antigens were detected in 2 of 10 (20%) field-captured Peromyscus leucopus from Tiverton Township, and in 41 of 355 (11.5%) dogs residing in Ohio. Collectively, these data suggest that the enzootic life cycle of B. burgdorferi has become established in Ohio, which poses risk of Lyme disease to people and animals in the area.